2012
DOI: 10.3109/09638237.2012.667885
|View full text |Cite
|
Sign up to set email alerts
|

Hell on earth: Textual reflections on the experience of mental illness

Abstract: People's experiences of being mentally ill might be understood as the result of medical constructions unsuitable for the persons themselves. We could instead say that mental problems are not diseases, but severe and painful phenomena in people's lives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 5 publications
0
23
0
1
Order By: Relevance
“…Despite the diverse objectives of studies on lived experience of mental illness, it is revealed that in most of them severely mentally ill people experience their disease as "a descent to hell" (Noiseux & Ricard, 2008, p. 1152, describing enormous suffering and exclusion from friends and families (Andersen & Larsen, 2012). The emotions frequently reported are shame, isolation (Liu, Ma, & Zhao, 2012) and powerlessness (Borg & Davidson, 2008).…”
Section: Introductionmentioning
confidence: 97%
“…Despite the diverse objectives of studies on lived experience of mental illness, it is revealed that in most of them severely mentally ill people experience their disease as "a descent to hell" (Noiseux & Ricard, 2008, p. 1152, describing enormous suffering and exclusion from friends and families (Andersen & Larsen, 2012). The emotions frequently reported are shame, isolation (Liu, Ma, & Zhao, 2012) and powerlessness (Borg & Davidson, 2008).…”
Section: Introductionmentioning
confidence: 97%
“…[1][2][3] The autobiographies represented a period of 90 years , but despite changing perspectives on treatment and different social and political eras, the experiences throughout the period were striking. The healthcare professionals were generally described as more interested in signs of illness than in the patient as a whole person with body and mind, hopes and dreams.…”
Section: Introductionmentioning
confidence: 99%
“…They emphasize these as fundamental for relationships between patients and professionals. It is crucial to understand people's problems as meaningful reactions to their life stories (11).…”
Section: Introductionmentioning
confidence: 99%